2009
DOI: 10.1159/000209346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoride on the Morphology of Calcium Phosphate Crystals Grown on Acid-Etched Human Enamel

Abstract: The aim of this study was to examine the effect of fluoride ion concentration on the morphology of calcium phosphate crystals grown on acid-etched enamel as a model for tooth enamel erosion. Samples were immersed in calcification solution for 16 h and changes in crystal morphology were monitored by field emission scanning electron microscopy. Without fluoride, plate-like octacalcium phosphate crystals (20 nm thick, 2–10 μm wide) were formed. With 1–10 mg/l fluoride, arrays of denser needle-like nanocrystals (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 57 publications
2
31
0
2
Order By: Relevance
“…However, other researchers have found that under controlled conditions, fluoride can be incorporated directly into the fluoridated hydroxyapatite grown on an etched enamel surface without the formation of spherical CaF 2 particles. 34 Thus, in our study, the results of the SEM observation manifested both phenomena.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, other researchers have found that under controlled conditions, fluoride can be incorporated directly into the fluoridated hydroxyapatite grown on an etched enamel surface without the formation of spherical CaF 2 particles. 34 Thus, in our study, the results of the SEM observation manifested both phenomena.…”
Section: Discussionsupporting
confidence: 70%
“…Fan's finding. 34 Many studies have demonstrated that calcium fluoride is a major reaction product after topical treatment with high fluoride concentrations. 20,35 Spherical CaF 2 precipitation can promote fluoride release and remineralization of enamel hydroxyapatite.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the phase formation and morphology of calcium phosphate crystals may be affected by temperature, ionic strength, pH, fluoride and supersaturation degrees 23, 24, 25. The change of solution supersaturation degree and fluoride concentration in mineralization solutions was reported to affect the crystal morphology dramatically 23, 26.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the F agent acidulated phosphate fluoride (APF) gel has been thought to cause minimal crystal dissolution and to exchange of OH with F ions under low pH condition [13][14][15][16][17][18][19] . Based on these conceptions, F schemes have been believed to improve the quality of tooth enamel for the past several decades 13) .…”
Section: Introductionmentioning
confidence: 99%